Spatio-temporal evolution law of gas-temperature coupling field in "110 method" goaf and prevention of spontaneous combustion. - Song Wei; Zhenqing Fang; Zongxiang Li; Yu Liu; Dongjie Hu; Chuntong Miao; Haiwen Wang (PLoS ONE, 2023)
To investigate the distribution characteristics of spontaneous combustion disaster (SCD) zones in the goaf of "110" mining method with U + L ventilation system and formulate corresponding fire prevention measures, enclosed coal oxidation experiments were carried out to measure the oxidation characteristics of Dongrong Coal Mine bituminous coal sample. A coupled 3DEC-CFD (3 dimensional Distinct Element Code) model was established. The 3D transient distribution characteristics of SCD zones in the "110" mining goaf under U+L ventilation condition were analyzed. Nitrogen injection in the tailgate was proposed for coal spontaneous combustion prevention. The results show that air leakage changed the distribution of oxygen and temperature fields in the "110" goaf, causing the region 20~60 m parallel to the retained roadway to remain in the oxidation zone for spontaneous combustion. As the working face advanced, the area change curve of SCD zones in the "110" goaf exhibited a "double inflection point" pattern. Eliminating the "retained roadway oxidation zone" can effectively reduce the spontaneous combustion risks in the "110" goaf and ensure mining safety. This study enriches the mechanisms of coal spontaneous combustion.